2017
DOI: 10.3389/fmicb.2017.00114
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Anti-Inflammatory Molecule (MAM) from Faecalibacterium prausnitzii Shows a Protective Effect on DNBS and DSS-Induced Colitis Model in Mice through Inhibition of NF-κB Pathway

Abstract: Faecalibacterium prausnitzii and its supernatant showed protective effects in different chemically-induced colitis models in mice. Recently, we described 7 peptides found in the F. prausnitzii supernatant, all belonging to a protein called Microbial Anti-inflammatory Molecule (MAM). These peptides were able to inhibit NF-κB pathway in vitro and showed anti-inflammatory properties in vivo in a DiNitroBenzene Sulfate (DNBS)-induced colitis model. In this current proof we tested MAM effect on NF-κB pathway in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
119
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(126 citation statements)
references
References 27 publications
2
119
2
3
Order By: Relevance
“…Interestingly, the results indicated that F. prausnitzii supernatant potentially regulates cell‐cell adhesion and the tight junction pathway, which are key to the intestinal barrier integrity. MAM, a newly discovered protein product of F. prausnitzii , shows anti‐inflammatory effects in the intestine in IBD . We questioned whether MAM could act on the intestinal barrier.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the results indicated that F. prausnitzii supernatant potentially regulates cell‐cell adhesion and the tight junction pathway, which are key to the intestinal barrier integrity. MAM, a newly discovered protein product of F. prausnitzii , shows anti‐inflammatory effects in the intestine in IBD . We questioned whether MAM could act on the intestinal barrier.…”
Section: Discussionmentioning
confidence: 99%
“…MAM, a newly discovered protein product of F. prausnitzii, shows anti-inflammatory effects in the intestine in IBD. 22,39 We questioned whether MAM could act on the intestinal barrier. Our results suggest that MAM potentially modulates numerous biological processes and signaling pathways of the intestinal epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…Tregs are abundant in the intestinal mucosa and are also modulated directly by bacterial antigens. For example, Faecalibacterium prausnitzii and Bacteroides fragilis, both common gut commensals, induced Treg activation and differentiation via the surface proteins, microbial anti-inflammatory molecule (MAM) and polysaccharide A (PSA), respectively (14,15). Both F. prausnitzii and B. fragilis are often missing or present at low abundancy in patients with IBD (16).…”
Section: Regulatory T Cells (Tregs)mentioning
confidence: 99%
“…92,93 In accordance with this, Quévrain et al 94 identified a 15 kDa anti-inflammatory protein was secreted by F. prausnitzii. Subsequently, a study by Breyner et al 95 demonstrated F. prausnitzii secreted peptides termed "microbial anti-inflammatory molecules" can inhibit nuclear factor (NF)-κB promoter activity and interleukin (IL)-6 production, leading to protection from experimental colitis in mice through alteration of T cell immune responses. Interestingly, co-culture studies have demonstrated F. prausnitzii does not enhance barrier function but can induce activation of NF-κB signaling downstream of IL-1β in Caco-2 cells.…”
Section: Faecalibacterium Prausnitziimentioning
confidence: 99%